Perancangan Pengalaman Pengguna Aplikasi Keuangan Organisasi berbasis Mobile (Studi Kasus : LO/LSO FILKOM UB) menggunakan Metode Design Thinking - Khairunnisa' Rahmadhanti; Buce Trias Hanggara; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Faculty of Computer Science (FILKOM) Brawijaya University (UB) has student organizations that can be used to accommodate the interests and talents of students which are divided into 2, namely Autonomous Institutions (LO) and Semi-Autonomous Institutions (LSO). The problem experienced by the treasurer of LO / LSO FILKOM UB is that the data collection of money in and out is still manual using several platforms. Too many platforms make the treasurer confused and less careful in recording so that data collection errors occur. Based on the existing problems, this research aims to create an organizational finance application user experience design that can help overcome the problems experienced by the treasurer and members of LO/LSO FILKOM UB. This design uses Design Thinking method because it focuses on users so it can overcome problems that are not yet clear. This research produces a mobile-based application design in the form of high-fidelity prototypes for two user segmentations. The resulting prototype was tested using the UEQ method to find out the design of the user experience designed has solved the problems of potential users. The test results are that the organizational finance application on both systems is in the positive category with a mean value range of 1.563 - 2.050.